Increased biological activity of protein Kinase C gamma is not required in Spinocerebellar ataxia 14 - Etsuko Shimobayashi; Josef P. Kapfhammer (Molecular Brain, 2017)
Abstract Spinocerebellar ataxia (SCA) is an autosomal dominant neurodegenerative disorder characterized by slowly progressive cerebellar dysfunction. Currently, 42 SCA types are known, some of which are caused by CAG repeat expansions, but others are caused by point mutations or deletions. Spinocerebellar ataxia type 14 (SCA14) is caused by missense mutations or deletions in the PRKCG gene, coding for protein kinase C gamma (PKCγ). It is still not well understood how these mutations eventually cause Purkinje cell dysfunction and death. Because PKCγ is a well characterized signaling protein highly expressed in Purkinje cells SCA14 offers the chance to better understand the pathogenesis of Purkinje cell dysfunction and death. Altered biological activity of PKCγ would be the simplest explanation for the disease phenotype. There are indeed indications that the enzymatic activity of mutated PKCγ proteins could be changed. Many mutations found in SCA14 families are located in the regulatory C1B and C1A domain, while a few mutations are also found in the C2 and in the catalytic C3 and C4 domains. For many of these mutations an increased enzymatic activity could be demonstrated in cell-based assays, but it remains unclear whether there is indeed an altered biological activity of the mutated PKCγ proteins within living Purkinje cells. In this study we used the dendritic morphology of developing Purkinje cells to detect increased biological activity of PKCγ after expression of different mutated PKCγ proteins. Our results indicate that two out of three known mutations in the catalytic domain of PKCγ did indeed show increased biological activity. On the other hand, none of the five tested mutations located in the regulatory C1 or the C2 domain showed an increased biological activity. Our findings indicate that SCA14 mutations located in different domains of the PRKCG gene cause SCA14 by different mechanisms and that an increased constitutive activity of PKCγ may be one, but cannot be the only mechanism to cause disease in SCA14.